Omental torsion at the time of COVID-19 in Northern Italy: a case report of conservative management with a review of the pertinent literature - Montali, Filippo; Costi, Renato; Virgilio, Edoardo; Presicci, Cristina; Sartorio, Carlotta; Pedrazzini, Massimo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: In middle-aged men, omental torsion (OT) can be a cause of acute abdomen.The right side of the omentum is longer, heavier and more mobile than the left one and, as a consequence, it can twist more easily on its vascular axis. Consequently, OT localization in the lower right quadrant is more frequent, and therefore it can mimic acute appendicitis clinical onset.In most cases, OT is defined as “primary” in the absence of any other underlying pathologies, or,  rarely, “secondary”, when caused by other intra-abdominal diseases such as inguinal hernia, tumors, cysts or post-surgical scarring. To date, clinical diagnosis of OT still remains a challenging one in a preoperative setting and most cases are diagnosed intraoperatively. If diagnosis is correctly achieved preoperatively by adequate imaging examinations, most patients presenting with OT do not undergo surgery anymore. Such considerations gain importance at the time of COVID 19 pandemic, where a conservative management and an early discharge may be preferred owing to in-hospital morbidity after abdominal surgery whenever surgery may be avoided.Methods and Results : We present a case of an OT successfully treated in a non-operative manner during COVID-19 outbreak in Norhern Italy and offer a review of the literature that supports such a clinical attitude. Conclusions:  OT preoperative diagnosis is challenging and is usually achieved by abdominal CT-scan. The suggested OT initial management is conservative, leaving a surgical approach, preferably by laparoscopy, for the 15% of cases not improving with a non-surgical approach.